Strategi Pengembangan Sumber Daya Manusia Melalui Metode Analisis SOAR pada Pariwisata Syariah di Pulau Madura - Farid Ardyansyah; Nasrulloh Nasrulloh (Jurnal Ilmiah Ekonomi Islam, 2022)
According to data from The Global Islamic Economy Report cited by Reuters (2015) predicts that it will increase in 2019 to 238 billion dollars and represent 13% of global contests. Projections of Muslim tourists will increase so that Madura Island, which is still just developing, is able to take advantage of these opportunities and can take advantage of one of the sharia tourism development destinations that must be able to take advantage of these opportunities and prove that the Madura economy is capable and competitive. Sharia tourism is a tourism concept that makes it easy for Muslim tourists to fulfill their travel needs. The analytical method used to formulate the strategy is SOAR analysis using a matrix that is adapted to research needs. The results of this study include 1) Planning and developing tourism through the creation of promotional media, both print media and social media that are integrated with the website to attract tourists and investors. 2) Rearrange and classify tourist objects by making clear, persuasive, informative and binding regulatory plans. 3) Madura Island tour packages in collaboration with relevant agencies or travel agents. 4) Creating training and coaching activities for local youth or synergizing with local communities in an effort to build excellent service. 5) Provide facilities and infrastructure that support Madura Island tourism comprehensively, such as a safe, communicative and integrated information service center. 6) Coordinate and map areas that are tailored to the needs and expected numbers. In addition, making regulations and coaching for owners of tourist agents, owners of inns/hotels or synergizing with the surrounding community.